Construction of Innovation and Entrepreneurship Education (IEE) System in Applied Universities: A Study Based on Practical Opportunities and University-Enterprise Collaboration - Zhou, Xianchao; Cheng, Yanbo; Tsetsgee , Bayasgalan; Tseveen , TS.; Jin, Peijian; Han, Bing (Journal of Education Culture and Society, 2025)
Aim. This study aims to construct a systematic Innovation and Entrepreneurship Education (IEE) system to enhance the comprehensive capabilities of applied universities in this area. Methods. The study employs surveys of students, teachers, and corporate representatives, along with in-depth interviews and case analyses, to investigate the key factors influencing the construction of such a system. A structural equation model is used to quantify the relationships between various factors, and the quantitative findings are supplemented and validated through case analysis. Results. The results indicate that increasing practical opportunities, deepening university-enterprise collaboration, and optimising course content are the core factors for improving the outcomes of IEE. Among these, practical opportunities have the most significant impact on enhancing students’ entrepreneurial abilities. Conclusion. This study not only provides theoretical support for constructing an IEE system in applied universities but also offers actionable and practical recommendations tailored to the Chinese context to promote the sustainable development of such education